Writing for the mass media - Stovall, James Glen (Pearson, 2012)
Writing for the Mass Media remains one of the clearest and most effective introductions to media writing available. This book offers clear writing, simple organization, abundant exercises, and precise examples that give you information about media writing and opportunities to develop your skills as a professional writer. With a focus on a converged style of media writing, and converting that style into real work, this eighth edition maintains its classic and effective text-workbook format while staying ahead of the curve and preparing professionals for their future careers.